Elevation, aspect, and habitat heterogeneity determine plant diversity and compositional patterns in the Kashmir Himalaya - Zishan A. Wani; Vikram S. Negi; Jahangeer A. Bhat; K. V. Satish; Ashish Kumar; Sajid Khan; Rupesh Dhyani; Sazada Siddiqui; Rahmah N. Al-Qthanin; Shreekar Pant (Frontiers in Forests and Global Change, 2023)
Elevational gradient, slope, and aspect offer a unique opportunity to explore the response of plant species under changing environmental conditions. The present study aimed to analyze the species diversity and distribution patterns with respect to altitude, aspect, and habitat types in the Kashmir Himalayas. Considering major aspects and habitats, a total of 123 representative sites were selected along the elevational gradients for the present study. The plant species composition of each selected site was studied by organized sampling following the standard ecological methods. During the present study, a total of 361 vascular plant species belonging to 71 families and 214 genera were identified in the study area. At the lower altitudes, the southern aspect and drier habitats showed the highest diversity. Moreover, a significant amount of compositional dissimilarity was observed between the studied aspects, habitats, and elevation belts and was mainly due to species turnover rather than the nestedness component. Further, among the studied variables, altitude was the most important contributing variable, explaining the greatest variation in the species composition. The paired effects of altitude and habitat explained the maximum variation in plant species composition. It may be concluded that floristic diversity should be studied not only with reference to elevational gradients but should also include aspects and habitats. The current study will act as a reference in this direction. A similar study must be replicated in other parts of the Himalayan region in the future to improve our understanding of the distribution and preferences of plant species in mountainous zones. This, in turn, will be immensely helpful in the conservation and sustainable utilization of resources in these ecologically fragile regions.